Kesalahan Penggunaan Kata Pelengkap Arah 出来Chūlái，出去 Chūqù，进来 Jìnlái, 进去jìnqù pada Mahasiswa Angkatan 2021 Prodi Pendidikan Bahasa Mandarin Universitas Negeri Surabaya - Zaaulhaq Zalzalah Zirly; Urip Zaenal Fanani (Pusat riset dan Inovasi Nasional, 2025)
Error checking is a technique for seeing mistakes made by students on the language object path. The aim of this research is to describe the forms of errors and factors that cause errors in the use of the complementary word 出来Chūlái，出去 Chūqù，进来 Jìnlái, 进去Jìnqù among students of the Class of 2021 Mandarin Language Education study program. This research uses descriptive and quantitative research instruments in the form of questions and questionnaires. The theory used in this research is Tarigan's theory. The research data in this study are errors in complementary words obtained from students' written and non-written exam answers. Formation errors were found in the part about filling in gapped sentences, the percentage of incorrect formation errors was 9.09%. Meanwhile, the word incorrectly arranged is found in the part about arranging random sentences into a correct sentence. The percentage of misordering errors is 61,82%. The cause of errors made by students is the lack of mastery of the material regarding the complementary words 出来Chūlái，出去 Chūqù，进来 Jìnlái, 进去Jìnqù as well as the complexity of the sentence structure which is very different from the structure of Indonesian.